Evaluation of 18F-DCFPyL PSMA PET/CT for Prostate Cancer: A Meta-Analysis - Pan, Ke-Hao; Wang, Jin-Feng; Wang, Chun-Ying; Nikzad, Abdul Aziz; Kong, Fang Q.; Jian, Li; Zhang, Yin-Qiu; Lu, Xiao-Ming; Xu, Bin; Wang, Ya-Li; Chen, Ming (Frontiers in Oncology, 2021)
Abstract Background: To systematically review the clinical value of 18F-DCFPyL prostate-specific membrane antigen positron emission tomography/computed tomography (PSMA PET/CT) in the diagnosis of prostate cancer(PCa) Methods: Literature concerning 18F-DCFPyL PSMA PET /CT in the diagnosis of prostate cancer published from 2015 to 2020 were electronically searched in the databases including PubMed and Embase. Statistical analysis was carried out with STATA 15 software, and the quality of included studies was tested with quality assessment of diagnostic accuracy studies( QUADAS) items. The heterogeneity of the included data was tested. Results: In total, nine pieces of literature involving 426 patients met the inclusion criteria. The heterogeneity of the study group was not obvious. The SEN, SPE, LR+, LR-, DOR as well as AUC of 18F-DCFPyL PSMA PET /CT diagnosis of prostate cancer were 0.91, 0.90, 8.9, 0.10, 93, and 0.93. The pooled DR of 18F--DCFPyL labeled PSMA PET/CT in PCa was 92%. The pooled DR was 89% for PSA≥0.5 ng/mL and 49% for PSA < 0.5 ng/mL. Conclusion: 18F-DCFPyL PSMA PET/CT had good sensitivity and specificity for the diagnosis of prostate cancer. The DR of 18F-DCFPyL PSMA PET/CT was correlated with PSA value. Further large-sample, high-quality studies were needed.